«Սասնայ ծռեր» էպոսը՝ իբրեւ արեւապաշտական դիցապատում - Ղազարեան, Նորայր (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Эпос «Сасна Црер» — это солнцепоклонническая система, герои которого являются воплощением солнечного мира. Действие эпоса в основном происходило в эпоху культа Митры. Два его героя, Большой и Малый Мгер, генеалогически связаны с богом Митрой. Идеалы Малого Мгера, выходящего из пещеры, восходят к идеологии, связанной со вторым пришествием Митры. Защита огня и воды начинается с первой ветви, в основе которой лежит миф о близнецах. Санасар и Багдасар — восходящее солнце, Большой Мгер и Давид — высшая точка, Малый Мгер — заходящее солнце. Герой последней ветви эпоса уединяется в Агравакаре (Вороний Камень). Ворон — символ солнца в мифологии. Это тотем — прародитель племени. Значит Малый Мгер, после выхода из пещеры, должен перейти в первозданный период мира. The “Daredevils of Sassoun” epic is a system of sun worship, the heroes of which are the embodiment of the sun myth. The epic was primarily created during the epoch of the cult of Mithras. Its two heroes — Lion (Great) Mher and Little Mher are in genealogical associations with the god Mithra. Ideals (visions) of Little Mher’s getting out of a crag (rock) were derived from the ideology associated with the second coming of Mithra. The worship of fire and water originates from the first branch, the basis of which is the Legend of the Twins. Sanasar and Baghdasar symbolize the ascending sun, Lion Mher and David — the zenith, and Little Mher - the descending sun. The hero of the last branch of the epic secludes himself in the Raven’s Rock (Agravakar). The Raven is the symbol of the sun in mythology. It is the totem, the progenitor of the tribe. Hence, before coming out, Little Mher shall return to the pre-creation period of the world.
Keywords: Բանասիրութիւն